Patients Prefer a Virtual Reality Approach Over a Similarly Performing Screen-Based Approach for Continuous Oculomotor-Based Screening of Glaucomatous and Neuro-Ophthalmological Visual Field Defects - Soans, Rijul Saurabh; Renken, Remco J.; John, James; Bhongade, Amit; Raj, Dharam; Saxena, Rohit; Tandon, Radhika; Gandhi, Tapan Kumar; Cornelissen, Frans W. (Frontiers in Neuroscience, 2021)
Standard Automated Perimetry (SAP) is the gold standard for evaluating the presence of visual field defects. Nevertheless, it has requirements such as prolonged attention, stable fixation and a need for a motor response that limit application in various patient groups. Therefore, a novel approach using eye movements (EM) – as a complementary technique to SAP - was developed and tested in clinical settings by our group. However, the original method uses a screen-based eye-tracker which still requires participants to keep their chin and head stable. Virtual reality (VR) has shown much promise in ophthalmic diagnostics - especially in terms of freedom of head movement and precise control over experimental settings, besides being portable. In this study, we set out to see if patients can be screened for visual field defects based on their EM in a VR-based framework and if they are comparable to the screen-based eyetracker. Moreover, we wanted to know if this framework can provide an effective and enjoyable user experience (UX) compared to our previous approach and the conventional SAP. Therefore, we first modified our method and implemented it on a VR head-mounted device with built-in eye tracking. Subsequently, fifteen controls naïve to SAP, fifteen patients with a neuro-ophthalmological disorder and fifteen glaucoma patients performed three tasks in a counterbalanced manner: 1) a visual tracking task on the VR headset while their EM was recorded, 2) the preceding tracking task but on a conventional screen-based eye tracker, 3) SAP. We then quantified the spatio-temporal properties (STP) of the EM of each group using a cross-correlogram analysis. Finally, we evaluated the human-computer interaction (HCI) aspects of the participants in the three methods using a user-experience questionnaire. We find that: 1) the VR framework can distinguish the participants according to their oculomotor characteristics; 2) the STP of the VR framework are similar to those from the screen-based eye tracker; 3) participants from all the groups found the VR-screening test to be the most attractive. Thus, we conclude that the EM-based approach implemented in VR can be a user-friendly and portable companion to complement existing perimetric techniques in ophthalmic clinics.